Analysis of heat transfer and fluid flow inside conventional and pent-roof type combustion chamber using dynamic mesh model - Varol, Yasin; Fırat, Müjdat (My University, 2011)
In this study, flow and heat transfer were investigated numerically the conventional type and roof type combustion chamber. Dynamic mesh model was used to analyzed in cylinder flow and heat transfer characteristics during intake stroke. k-? turbulence model was chosen for the solution equations of turbulence. Governing equations were solved with finite volume method and FLUENT-12.0 commercial software. The results were expressed in the inner velocity profile and temperature distribution, and comparison to both type chamber are presented. Heat transfer and flow characteristics of the roof type combustion chamber for better performance than conventional type combustion chamber showed.
Bildiri - Yayımlanmış
Keywords: İçten Yanmalı Motorlar; Yanma Odası